Development of a textile-based smart wearable for enhanced galvanic skin response monitoring - Ang, Jun Ming (Nanyang Technological University, 2024)
The objective of this Final Year Project (FYP) is to explore the possibility of developing smart wearables incorporated into textile products, with a focus on galvanic skin response (GSR) monitoring. In addition to making use of such biometric signals to characterize the well-being of an individual, this project aims to explore the possibility of obtaining such signals non-invasively, ensure reliable collection, as well as their subsequent interpretation.